Cooperative Accounting Training and Preparation of Financial Reports for Managers/Administrators of The Banten 1 Suralaya Employee Cooperative of Steam Power Plant: Pelatihan Akuntansi Koperasi dan Penyusunan Laporan Keuangan Bagi Pengurus/Pengelola Koperasi Karyawan PLTU Banten 1 Suralaya - Tri Susmita, Silvia; Nurkholis, M.; Lazuarni, Shafiera (Universitas Haji Sumatera Utara, 2025)
A cooperative is a business entity owned and operated by individuals or legal entities for the common interest. Cooperatives play an important role in the people's economy. To encourage the growth and development of cooperatives, training is needed to enhance the capacity of cooperative managers. This Community Service activity aims to provide assistance to the accounting and finance department of the Cooperative, particularly for the Employee Cooperative of PLTU Banten 1 Suralaya, in recording and reporting its financial transactions. The method used in this community service is training and assistance in preparing the Cooperative's financial statements. Participants in this training are the management of the Employee Cooperative of PLTU Banten 1 Suralaya. The activity consists of three phases: planning, implementation, and evaluation. The training will be conducted over one day, specifically on July 26, 2024. The results of this activity are expected to benefit the Employee Cooperative of PLTU Banten 1 Suralaya by improving the management of financial transactions, which will ultimately increase the income of the Cooperative.